DOM 2022 : using the DOM and JavaScript to build dynamic websites. (Packt Publishing, 2022)
From the beginning to the end, learn and master the DOM (Document Object Model) in simple steps About This Video Learn how your website can come alive with actions, such as zitsy changes on click, color wheel, drop down, response on form submissions, and much more Build awesome dynamic front-end applications Become a pro at listening for events that are fired In Detail In the first half of the course, we will cover everything you need to start coding dynamic sites by yourself. It gives you the sound fundamentals and essential practical regarding the DOM. You will emerge from part 1 with a basic understanding and practical experience. It will take you to the point where you will understand what the DOM is, why we need it, how to access it, where to find it, and how to manipulate it. By the end of part 1, you will have learned about front-end web development by mastering the Document Object Model. The second half of the course provides a whole different world of fun with amazing practical examples that will captivate you and catapult you to the next level and set you well on your way to becoming a true Grandmaster in front-end web development. By the end of part 2, you will have learned more about front-end web development by working with events in the Document Object Model. By the end of this course, you will be able to "speak" and "walk" DOM by gaining an understanding of how you can manipulate it in meaningful and practical ways. Audience It makes no difference where you are on your web development path. This course is appropriate for all skill levels. If you want to become a full-stack web developer or construct dynamic, fascinating, and acclaimed websites, this course is for you. Basic HTML, CSS, and JavaScript will be useful, but they are not required.